2015
DOI: 10.1002/ece3.1650
|View full text |Cite
|
Sign up to set email alerts
|

Conspicuous male coloration impairs survival against avian predators in Aegean wall lizards, Podarcis erhardii

Abstract: Animal coloration is strikingly diverse in nature. Within‐species color variation can arise through local adaptation for camouflage, sexual dimorphism and conspicuous sexual signals, which often have conflicting effects on survival. Here, we tested whether color variation between two island populations of Aegean wall lizards (Podarcis erhardii) is due to sexual dimorphism and differential survival of individuals varying in appearance. On both islands, we measured attack rates by wild avian predators on clay mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 87 publications
1
36
0
Order By: Relevance
“…Sometimes accuracy of appearance is vital, when the models are intended to look, to predators, like a particular species or local variant of a species. Marshall, Philpot & Stevens () used reflectance spectrometry measurements of Aegean wall lizards Podarcis erhardii to alter the colour of the clay used to make lizard models in an effort to mimic the colour as part of their test for the contribution of sexual dimorphism and local variation to predation rates by birds. Similarly, Stuart‐Fox et al .…”
Section: Interpretation and Problemsmentioning
confidence: 71%
“…Sometimes accuracy of appearance is vital, when the models are intended to look, to predators, like a particular species or local variant of a species. Marshall, Philpot & Stevens () used reflectance spectrometry measurements of Aegean wall lizards Podarcis erhardii to alter the colour of the clay used to make lizard models in an effort to mimic the colour as part of their test for the contribution of sexual dimorphism and local variation to predation rates by birds. Similarly, Stuart‐Fox et al .…”
Section: Interpretation and Problemsmentioning
confidence: 71%
“…Furthermore, higher predator attacks on male models compared to females were not due to their larger size. One of the central predictions of sexual selection is that males, and not females, are expected to express conspicuous colours [3] as males have greater selection pressure to signal to competitors and mates [26,27]. As demonstrated here, conspicuous colours can have a significant predation cost.…”
Section: Discussionmentioning
confidence: 90%
“…Sexual selection is therefore insufficient to explain all the variation in sexual dichromatism. Second, in natural populations of lizards predators were shown to prefer more colorful males (Stuart-Fox et al 2003, Marshall et al 2015, and in detailed studies of fish, males were subsequently less brightly colored in populations suffering higher risk of predation (Endler 1980, 1983, 1991, Ruell et al 2013. His view has recently been supported by two observations.…”
mentioning
confidence: 92%
“…First, detailed phylogenetic studies of several avian clades suggested that dichromatism arose due to females becoming less conspicuous rather than males becoming brighter (Friedman et al 2009, Dale et al 2015. Second, in natural populations of lizards predators were shown to prefer more colorful males (Stuart-Fox et al 2003, Marshall et al 2015, and in detailed studies of fish, males were subsequently less brightly colored in populations suffering higher risk of predation (Endler 1980, 1983, 1991, Ruell et al 2013. Generally, if the strength, or even direction, of selection pressure on coloration is different for males and females, the evolutionary outcome should be sexual dichromatism (Cox and Calsbeek 2009).…”
mentioning
confidence: 99%